KEPEMIMPINAN ALTRUISTIK DAN KEBAHAGIAAN DI TEMPAT KERJA - Nurrahman, Nurrahman; Donal Devi Amdanata (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The research method uses library research, by collecting data from various literature related to the research topic. This study aims to explore the relationship between altruistic leadership and happiness in the workplace, addressing this research gap. Based on Social Exchange Theory, this study investigates how altruistic leadership influences employees' workplace happiness from a holistic perspective. These findings contribute valuable insights to management studies, particularly in leadership, organizational behavior, and human resource management. Additionally, this research underscores the importance of altruistic leadership in fostering positive and happy workplace behavior among employees, providing guidance for organizational management to design strategies that increase workplace happiness.